The dangerous biology of pathogenic germs - Berche, Patrick (Comptes Rendus Biologies, 2024)
The convergence of biotechnologies with other disciplines, including computer science and Artificial Intelligence (AI), may make it possible to carry out dangerous genetic manipulations on pathogenic germs, as the gain-of-function experiments exacerbating virulence, as those carried out on myxoviruses and coronaviruses. Moreover, it is now possible to chemically synthesise any microorganism from in silico sequences, including the most dangerous viruses (poxviruses, Ebola, etc.), whose sequences are accessible. It might even be possible to use AI to design new germs that could be used as biological weapons.